Dichotomous histopathological assessment of ductal carcinoma in situ of the breast results in substantial interobserver concordance. Issue 6 (22nd October 2018) - Van Bockstal, Mieke; Baldewijns, Marcella; Colpaert, Cécile; Dano, Hélène; Floris, Giuseppe; Galant, Christine; Lambein, Kathleen; Peeters, Dieter; Van Renterghem, Sofie; Van Rompuy, Anne‐Sophie; Verbeke, Sofie; Verschuere, Stephanie; et al.
Abstract : Aims: Robust prognostic markers for ductal carcinoma in situ (DCIS) of the breast require high reproducibility and thus low interobserver variability. The aim of this study was to compare interobserver variability among 13 pathologists, in order to enable the identification of robust histopathological characteristics. Methods and results: One representative haematoxylin and eosin‐stained slide was selected for 153 DCIS cases. All pathologists independently assessed nuclear grade, intraductal calcifications, necrosis, solid growth, stromal changes, stromal inflammation, and apocrine differentiation. All characteristics were assessed categorically. Krippendorff's alpha was calculated to assess overall interobserver concordance. Cohen's kappa was calculated for every observer duo to further explore interobserver variability. The highest concordance was observed for necrosis, calcifications, and stromal inflammation. Assessment of solid growth, nuclear grade and stromal changes resulted in lower concordance. Poor concordance was observed for apocrine differentiation. Kappa values for each observer duo identified the 'ideal' cut‐off for dichotomisation of multicategory variables. For instance, concordance was higher for 'non‐high versus high' nuclear grade than for 'low versus non‐low' nuclear grade. 'Absent/mild' versus 'moderate/extensive' stromal inflammation resulted in substantially higher concordance than other dichotomous cut‐offs. Conclusions: Dichotomous assessment of the histopathological features of DCIS resulted in moderate to substantial agreement among pathologists. Future studies on prognostic markers in DCIS should take into account this degree of interobserver variability to define cut‐offs for categorically assessed histopathological features, as reproducibility is paramount for robust prognostic markers in daily clinical practice. A new prognostic index for DCIS might be considered, based on two‐tier grading of histopathological features. Future research should explore the prognostic potential of such two‐tier assessment.